Pengaruh Dukungan Teman Sebaya Dan Kelekatan Orang Tua Terhadap Perilaku Prososial Pada Siswa SMP - Tria Fitriana; Octa Reni Setiawati; Prida Harkina (Nathiqiyyah, 2025)
This study aims to explore the extent to which peer support and parental attachment influence prosocial behavior in junior high school students. Prosocial behavior refers to voluntary acts intended to assist others without expecting any compensation. During early adolescence, peer relationships and parental bonds are recognized as key contributors to the development of prosocial tendencies. The research applied a quantitative correlational method, involving 100 students from Mutiara Bangsa Junior High School in Bandar Lampung, selected through a quota sampling technique. Data were gathered using three instruments: the Prosocial Behavior Scale, Peer Support Scale, and Parental Attachment Scale. The results, analyzed using multiple linear regression, revealed that peer support and parental attachment together significantly affect prosocial behavior (F = 80.659; p < 0.05) with a determination coefficient (R²) of 0.624. However, when tested individually, only peer support had a statistically significant effect, while parental attachment did not (p > 0.05). These findings underscore the stronger influence of peer connections in shaping prosocial behavior compared to parental attachment during early adolescence.